THREE TYPES OF VARIATIONAL RELATION PROBLEMS - Balaj, Mircea (Taiwanese journal of mathematics, 2013)
Variational relation problems were introduced by Luc in [1] as a general model for a large class of problems in nonlinear analysis and applied mathematics. Since this manner of approach provides unified results for several mathematical problems it has been used in many recent papers (see [2-9]). In this paper we investigate the existence of solutions for three types of variational relation problems which encompass several generalized equilibrium problems, variational inequalities and variational inclusions studied in a long list of papers in the field. 2010Mathematics Subject Classification: 49J53, 54H25. Key words and phrases: Variational relation problem, Variational inequality, KKM theorem, Fixed point.